The simultaneous sponsorship of rival teams: Beyond ingroup favoritism and outgroup animosity. Issue 1 (2nd September 2021) - Bee, Colleen; Dalakas, Vassilis; Chen, Johnny
Abstract: The current research broadens the scope of sponsorship research to empirically examine ambivalence as a consumer response to the increasingly popular strategy of brands engaging in the simultaneous sponsorship of rival teams (i.e., a joint sponsorship). Specifically, our research considers the effects of ambivalence and team identification on sponsorship responses across three different types of brand‐team partnerships: a joint sponsorship of two rival teams, a favored team sponsorship, and a rival team sponsorship. Our results indicate that a joint sponsorship elicits ambivalence which directly and indirectly has a negative impact on attitudes and intentions toward the sponsoring brand. Joint sponsorships were also found to diminish the well‐established link between team identification and attitudes and intentions. Our research also identified argument strength as a brand messaging strategy for mitigating some of the negative effects of simultaneously sponsoring rival properties.